2008
DOI: 10.1111/j.1600-0609.2008.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal isoimmune thrombocytopenia caused by type I CD36 deficiency having novel splicing isoforms of the CD36 gene

Abstract: Neonatal alloimmune thrombocytopenia (NAIT) occurs because of transplacentally acquired maternal platelet alloantibodies. Most of the alloantibodies are against human platelet antigens, but the alloantibody against CD36 is rare. A full-term female baby was delivered by a mother who experienced two spontaneous abortions. The baby had thrombocytopenia with cephalhematoma. The platelet count increased by immunoglobulin therapy (400 mg/kg) for 3 d. Platelet antibody was detected in the postpartum maternal serum. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…28 Interestingly, variable clinical pictures of FNAIT mediated by anti-CD36 isoantibodies, including mild and severe thrombocytopenia, hydrops fetalis, and recurrent abortions, have been observed. [9][10][11][12][13]29 However, the precise mechanism of this phenomenon is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Interestingly, variable clinical pictures of FNAIT mediated by anti-CD36 isoantibodies, including mild and severe thrombocytopenia, hydrops fetalis, and recurrent abortions, have been observed. [9][10][11][12][13]29 However, the precise mechanism of this phenomenon is not known.…”
Section: Discussionmentioning
confidence: 99%
“…6 The clinical importance of anti-CD36 isoantibodies in the development of FNAIT has been reported in different populations. [9][10][11][12][13] Currently, the antigen-capture assay represents the gold standard for detecting platelet antibodies. 14 With this assay, platelet antigens captured by mouse monoclonal antibody are used as the target for platelet antibodies.…”
mentioning
confidence: 99%
“…In the Chinese population, the frequency of type I was found to be around 0Á5% [12,17]. Although the overall frequency of immunization against CD36 is not known yet, several PTR and FNAIT cases have been recently reported in the Chinese population [12,18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to HPA antigens, antibodies against CD36 glycoprotein a member of class B scavenger receptor family [58] is also implicated in the causal of FNAIT. A case study reported, maternal deficiency in expression of CD36 protein lead to maternal immunization against CD36 protein (anti-NAK) [59]. The clinical impact of NAIT is related with maternal immunization against CD36 is analogous to that observed in infants affected by HPA specific antibodies [60].…”
Section: Foetal/neonatal Alloimmune Thrombocytopenia (Fnait)mentioning
confidence: 94%